Work experience during higher education and post-graduation occupational outcomes: A comparative study on four European countries. (June 2015) - Passaretta, Giampiero; Triventi, Moris
This article examines the relationship between work experience acquired during higher education and post-graduation labour market outcomes in four European countries: Germany, Italy, Norway and Spain. A theoretical framework that shows in which institutional contexts work experience may be a 'competitive advantage' for young graduates is developed. In the empirical analysis, data from the Higher Education and Graduate Employment in Europe (CHEERS) and Research into Employment and Professional Flexibility (REFLEX) surveys are used to examine the effect of a typology of student employment (accounting for both length and coherence of work experience with the field of study attended) on several occupational outcomes 4–5 years after graduation. The empirical results show that, in Italy and especially in Spain, work activities during tertiary education are associated with better labour market positions after graduation: any type of work experience increases employability and reduces the risk of unemployment, and furthermore, previous work experience – especially when coherent with the field of study – decreases the probability of skill mismatch in future occupations. The effect of student employment, however, is smaller for most outcomes in Germany and negligible in Norway.